Effect of Therapeutic Plasma Exchange on Immunoglobulin Deficiency in Early and Severe Septic Shock. (December 2021) - Stahl, Klaus; Bikker, Rolf; Seeliger, Benjamin; Schmidt, Julius J.; Schenk, Heiko; Schmidt, Bernhard M. W.; Welte, Tobias; Haller, Hermann; Hoeper, Marius M.; Brand, Korbinian; David, Sascha
Background: Deficiency of immunoglobulins of the classes IgG, IgG1, IgA and IgM is associated with severity of disease and mortality in sepsis and septic shock. Therapeutic plasma exchange (TPE) with fresh frozen plasma (FFP) has recently gained attention as an adjunctive therapeutic option in early septic shock. We hypothesized that TPE might modulate immunoglobulin deficiencies besides sole elimination of circulating injurious molecules. Methods: We conducted a prospective single center study with TPE in 33 patients with early septic shock (onset < 12 h) requiring high doses of norepinephrine (NE > 0.4μg/kg/min). Clinical and biochemical data, including measurement of immunoglobulin subgroups IgG, IgG1, IgM and IgA were obtained before and after TPE. The following immunoglobulin cut-off values were used to analyze subgroups with low immunoglobulin concentrations at baseline (IgG ≤ 6.5, IgG1 ≤ 3, IgM ≤ 1.5 and IgA ≤ 0.35 g/L). Results: At inclusion, median (IQR) SOFA score was 18 (15-20) and NE dose was 0.8 (0.6-1.2) μg/kg/min. The majority of patients demonstrated profound reductions in immunoglobulins levels of all classes. Globally, immunoglobulin levels were not significantly changed after a single TPE session. However, in patients with low baseline immunoglobulin levels a significant increase in all classes was observed (IgG 1.92 (0.96-3) g/L (+41%), IgG1 2.1 (1.46-2.32) g/L (+96%), IgA 0.44 (0.12-0.62) g/L (59%) and IgM 0.18 (0.14-0.34) g/L (+55%), p < 0.001 for comparison to patients above cut-off). Conclusions: The majority of early and severe septic shock patients had reduced immunoglobulin levels and a single TPE could attenuate immunoglobulin deficiencies of all classes. The clinical relevance of this observation has to be investigated in a proper designed trial.